2010
DOI: 10.1002/ppul.21153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on pulmonary surfactant proteins A and D in ovine lung epithelia

Abstract: SummaryMaternal smoking during pregnancy increases the incidence and severity of respiratory infections in neonates. Surfactant proteins A and D (SP-A and SP-D, respectively) are components of pulmonary innate immunity and have an important role in defense against inhaled pathogens. The purpose of this study was to determine if nicotine exposure during the third trimester of pregnancy alters the expression of SP-A and SP-D of fetal lung epithelia. Pregnant ewes were assigned to four groups; a nicotine-exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In animal studies, prenatal nicotine exposure has been shown to increase surfactant mRNA and protein in mice, rats, monkeys, and lambs (52,56,65,66). Consistent with this, nAChRs are expressed on type II cells (56).…”
Section: Effects Of Prenatal Nicotine Exposure On Lung Development Anmentioning
confidence: 53%
“…In animal studies, prenatal nicotine exposure has been shown to increase surfactant mRNA and protein in mice, rats, monkeys, and lambs (52,56,65,66). Consistent with this, nAChRs are expressed on type II cells (56).…”
Section: Effects Of Prenatal Nicotine Exposure On Lung Development Anmentioning
confidence: 53%
“…Increased sFas serum concentration in prenatal and early postnatal, possibly indicates gradual decrease of proliferation and apoptosis in early postnatal life [8,9]. The maternal nicotine exposure during last trimester of pregnancy alters a key component of lung innate immunity in offspring [10]. Specific cell adhesion molecules are important to lung development and airway morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, altered surfactant release has been shown to play an important role in reduced lung compliance. Interestingly, in rat pups prenatally exposed to CS, a reduced dynamic compliance was measured ( 93 ), while decreased surfactant protein A levels in BALF were observed in ewes prenatally exposed to nicotine ( 94 ). The underlying mechanism by which prenatal and postnatal CS exposure affects children’s lung health is not defined yet.…”
Section: Discussionmentioning
confidence: 99%